Processive extrusion of polypeptide loops by a Hsp100 disaggregase - Avellaneda, Mario; Franke, Kamila B.; Bukau, Bernd; Mogk, Axel (Nature, 2020)
A combination of optical tweezers and fluorescent-particle tracking is used to dissect the dynamics of the Hsp100 disaggregase ClpB, and show that the processive extrusion of polypeptide loops is the mechanistic basis of its activity.
Das PDF enthält zusätzlich einen Anhang von 15 Seiten
Gesehen am 31.01.2020